Diagnosis of solidarity organizations of the artistic-cultural sector in Córdoba and Sucre (2020)
This study from the creative and solidarity economy industries, aimed to diagnose the artistic-cultural solidarity organizations in the Colombia´s department Córdoba and Sucre, by reviewing external and internal factors, to expand possible channels in their development; the assisted questionnaires validated by Artesanías de Colombia and the business solidarity entities of Alfaro (2017) were applied in 103 entities. In the results of the diagnostic matrix, external factors had a score of 2.9 and internal factors 2.56; indicating that they are below the average level of cultural industries. In the synthesis of strategic factors the result was 3.0, within the average of the cultural industry; internally, the plurality and ethnic diversity in the composition of the associates, high creativity and medium expertise stand out. The main findings for the external, allow to recommend in the short term to participate in the integral program of rural cooperative solidarity intervention, participation in tourism from the cultural and heritage perspective promoting creative vocations. Future research should be considered from the development of capacities in innovation and sustainable intelligence. © 2020, Universidad del Zulia. All rights reserved.